Culture and tax structures - Tobias König; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2012)
We argue that societies with a stronger tendency towards postmaterialist life goals tilt the tax structure towards personal income taxes and away from corporate taxation. We provide empirical evidence for this correlation in OECD countries. To address endogeneity issues we then use an epidemiological approach and employ the cultural values of second-generation immigrants to the US as an instrument for the degree of postmaterialism in their ancestral countries. Estimations with this approach re-confirm that personal taxes are higher, both in absolute and relative terms, in more postmaterialist countries.
Keywords: H11; H20; Z10; 330; tax structure; taxation; social values; culture; Steuersystem; Soziale Werte; Postmaterialismus; Einkommensteuer; Theorie; Schätzung; Migranten; Generationenbeziehungen; USA